EXOGENOUS ENZYMES AND PELLETING INCREASE DIET DIGESTIBILITY OF PIGLETS - Cruz, Thiago Augusto; Stresser, Aimée Caroline Pereira; Oliveira, Simone Gisele; Almeida, Leopoldo Malcorra; Santos, Marley Conceição; Félix, Ananda Portella (Archives of Veterinary Science, 2020)
In view of the need to increase food production to meet growing world demand, technologies must be developed to improve the performance of animals for human consumption. In this sense, studies with enzymes inclusion and feed processing have been done in order to improve food efficiency and, consequently, the animal production result. In order to verify the digestibility of complex commercial diets in the pre-initial stage of piglets submitted to the inclusion of an enzymes mixture and or pelletizing, were used 24 castrated male pigs with average age of 35 days and mean weight of 8 kg. The animals were individually housed in metabolism cages and submitted to four treatments: mash diet, mash diet with enzymes, pelleted diet and pelleted diet with addition of the enzyme mixture. After adaptation of the piglets to the diets for seven days, feces were collected for five days for the digestibility trials. The collection method was total collection of feces. There was interaction for digestible energy, crude protein, dry matter and ether extract (P>0.05). Pelleting and inclusion of the enzymatic complex allowed an increase in the coefficient of digestibility in all evaluated parameters (P<0.05). Therefore, the enzyme mixture tested and the pelleting can be used as artifice to increase the digestibility of commercial diets for piglets in the pre-initial phase.